THE QUALITY OF LIFE OF LIVING LIVER FRAGMENT DONORS - V. K. Konstantinov; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2016)
Quality of Life is a new promising area of clinical medicine that provides the opportunity to assess the state of health of the patient using the data stored across a joint professional approach of physicians and subjective point of view of patients. Review of the data of foreign and domestic literature on quality of life of living donor liver transplantation is done. A method for evaluating quality of life of the most commonly used questionnaires in the study of quality of life is described. The article deals with the history of the study of the quality of life in medical practice. Research results into the quality of life of living donor liver transplantation conducted in different countries are presented. Factors affecting the change in the quality of life of living donor liver transplantation are shown.